2012
DOI: 10.1104/pp.112.201459
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Rubisco Small Subunit Up-Regulates the Transcript Levels of Large Subunit for Stoichiometric Assembly of Its Holoenzyme in Rice

Abstract: Rubisco is composed of eight small subunits coded for by the nuclear RBCS multigene family and eight large subunits coded for by the rbcL gene in the plastome. For synthesis of the Rubisco holoenzyme, both genes need to be expressed coordinately. To investigate this molecular mechanism, the protein synthesis of two subunits of Rubisco was characterized in transgenic rice (Oryza sativa) plants with overexpression or antisense suppression of the RBCS gene. Total RBCS and rbcL messenger RNA (mRNA) levels and RBCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 63 publications
4
47
0
Order By: Relevance
“…In our study, RBCL and RBCS showed a common expression pattern (Table 5), confirming the coordinated expression of both subunits necessary for the assembly of the Rubisco holoenzyme (Suzuki and Makino, 2012). At the first sampling date, gene expression of RBCL and RBCS was down-regulated in response to elevated [CO 2 ] no matter which water regime was considered, in agreement with other wheat studies (Aranjuelo et al, 2013; Habash et al, 2014; Vicente et al, 2015b).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our study, RBCL and RBCS showed a common expression pattern (Table 5), confirming the coordinated expression of both subunits necessary for the assembly of the Rubisco holoenzyme (Suzuki and Makino, 2012). At the first sampling date, gene expression of RBCL and RBCS was down-regulated in response to elevated [CO 2 ] no matter which water regime was considered, in agreement with other wheat studies (Aranjuelo et al, 2013; Habash et al, 2014; Vicente et al, 2015b).…”
Section: Discussionsupporting
confidence: 85%
“…Chlorophyll content only increased under elevated [CO 2 ] in Mexa at the first sampling date, but the effect disappeared at the second sampling (Table 3). [CO 2 ] enrichment and water stress did not modify C content in leaves, suggesting that the decrease in N content was not simply due to N dilution caused by rapid growth (Taub and Wang, 2008). Overall, our data showed that the decrease in N content in plants grown under elevated [CO 2 ] and water stress during vegetative growth is genotypically dependent.…”
Section: Discussionmentioning
confidence: 99%
“…When the mRNA levels and protein synthesis of Rubisco subunits in young, expanding leaves were compared among RBCS -sense, RBCS -antisense, and wild-type plants, the RBCL mRNA level was observed to be tightly correlated not with RBCS mRNA levels but with the amount of synthesized RBCS protein (Suzuki and Makino, 2012). In contrast to tobacco, polysome loading of RBCL mRNA was relatively unaffected, even in RBCS -antisense plants.…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of the rbcS gene slightly upregulates the gene expression of rbcL at the transcript level and enhances the amount of RuBisCo holoenzyme (Suzuki and Makino 2012). This might be expected to improve the photosynthetic efficiency of chitosan-treated rice and so facilitate the enhanced plant growth rate.…”
Section: Chitosan Stimulated Plant Carbon Metabolism and Photosynthesmentioning
confidence: 96%